The Influence of Individual Factor (Machievallian) on Ethical Decision Making Among Civil Servants - Md Ali, Azlah; Mohamed Saat, Maisarah; Abu Bakar, Thuaibah; saleh, nor shela; Rosli, Mohd Shafie (Journal of Social Transformation and Regional Development, 2021)
This study explores the influence of individual factor (machiavellian) on ethical decision making among civil servants in federal, state and local government agencies and are members of Majlis Mesyuarat Pusat Setempat and located in all 16 Local Authorities (PBT) in Johor. In doing so, it employed the Rest’s Ethical Decision Making Model (1986). The findings of the study showed that individual factors (machiavellian) have an influence on all four stages of ethical decision making (ethical awareness, ethical judgement, ethical intention and ethical behavior) among respondents. The high mach element was found to be more dominant in all four stages of ethical decision making rather than the low mach element. Using alternative methodologies and adding the independent variables and other elements, may aid future research in complementing these results, thus provide an enhanced understanding of civil servants’ ethical decision making.